2004
DOI: 10.1007/s00134-004-2196-6
|View full text |Cite
|
Sign up to set email alerts
|

Hidden evidence to the West: multicentre, randomised, controlled trials in sepsis and systemic inflammatory response syndrome in Japanese journals

Abstract: Despite sound methodology and quality, the information obtained from relatively large Japanese critical care trials is not widely available to English-speaking investigators and therefore might be ignored in meta-analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Titles of the 215 references were scanned for relevance, based on the inclusion criteria, and this identified 48 references as potentially relevant. Abstracts of the 48 references (available from the authors on request) were scanned for relevance, again based on the inclusion criteria, and this identified 12 references [42][43][44][45]53,56,59,[60][61][62][63][64] as potentially relevant. Full-text copy was obtained for each of the 12 references and, of these, six [42][43][44][45]53,56 were already identified from the six previous systematic reviews.…”
Section: Literature Searching/inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Titles of the 215 references were scanned for relevance, based on the inclusion criteria, and this identified 48 references as potentially relevant. Abstracts of the 48 references (available from the authors on request) were scanned for relevance, again based on the inclusion criteria, and this identified 12 references [42][43][44][45]53,56,59,[60][61][62][63][64] as potentially relevant. Full-text copy was obtained for each of the 12 references and, of these, six [42][43][44][45]53,56 were already identified from the six previous systematic reviews.…”
Section: Literature Searching/inclusion Criteriamentioning
confidence: 99%
“…Full-text copy was obtained for each of the 12 references and, of these, six [42][43][44][45]53,56 were already identified from the six previous systematic reviews. Of the remaining six, 59-64 one 60 was a duplicate reference and five 59,[61][62][63][64] failed to meet the inclusion criteria for our current review ( Table 5). In summary, no new studies were identified for inclusion to update the existing systematic review.…”
Section: Literature Searching/inclusion Criteriamentioning
confidence: 99%
“…Among 8 articles we chose for the meta-analyses, 4 are written in Japanese and none of them are found on MED-LINE, EMBASE, or Cochrane Database of Systematic Reviews. It was pointed out that RCTs found in ICHUSHI may have good quality by CONSORT checklist but might be ignored by English-speaking investigators (27). In our analyses, extensive literature search was done for both English and Japanese articles.…”
Section: Discussionmentioning
confidence: 99%
“…F i g u r e 1 . Ch e s t CT o n a d mi s s i o n ( A) a n d a f t e r s i v e l e s t a t a n d a n t i t u b e r c u l o s i s t h e r a p y ( B ) among patients with lung injury associated with SIRS (2). Therefore, we believe that sivelestat sodium hydrate combined with antituberculosis therapy presents a novel therapeutic option in the treatment of ARDS due to tuberculosis.…”
Section: The Hematogenous Spread Of Mycobacterium Tuberculosis Causesmentioning
confidence: 99%